Relacje i środki trwale- praca-wyniki gospodarowania w drobnej wytwórczości - Gawrzyński, Janusz (Wydział Prawa i Administracji UAM, 1968)
The author discussing the individual measures of results of economic activity emphasises the specific role of financial accumulation as a quality measure of this activity. In the relation capital assets — labour — financial accumulation or profits work input is illustrated in the farm of payment funds by which the relation may expressed in a uniform value expression. The comparison of relations shows, in the field of economy and organizing units in which activities for the demands of the home market predominate, lower variability of accumulation indicators than those of profit. This variability results firstly from the fundamental duty of the economic unit paying turnover tax. The relations, capital assets — labour — financial accumulation are expedient instruments in a comparative analysis of economic effects. The accuracy of these effects depends to a large extent, on the system of prices, however when taking into consideration the deforming activities of a closer field the influence of the price system decreases. The attempt at examining these relations in small industry seems to indicate in practice the need of increasing the degree of technical labour equipment in cooperatives, which is possible i. a. by way of maximum utilization of non-limited investments. The comparison of relations also confirms the need of assurance on the part of industry organizations for a greater degree of organized industry activity.
Relation of Capital Assets-Labour- Economic Effects in Small Industry